Accessible housing guidelines: A global comparison - Amar, Muhammad Ramli; Liyana, Mohamed Yusof; Rahimi, A. Rahman; Azlina, Ismail (AIP Publishing, 2023)
House is one of the most important necessities in one’s life. Houses with good accessibility parameters will be able to improve the life quality of the occupants regardless of age and abilities and support the aging process. Hence, guidelines related to accessibility in housing have been developed globally, respectively, either by the countries’ governments or as initiatives of its housing developers. Therefore, this research aims to determine and explore the current guidelines on accessibility in housing from several countries. In response, the research employs a qualitative approach by comparing these guidelines to develop a suitable accessibility guideline for the context of Malaysian housing. The findings determine the important spaces are: bathroom; building entrance; circulation/corridor; kitchen; bedroom and; access to the site. Furthermore, the important categories for each element are: size; accessibility; materials; safety; comfort, and; fitting. These findings are hoped to assist local authorities, developers, and professionals in improving the housing development in Malaysia, in particular to accessibility aspects.